Relationship between personality type, aggressive behaviour and self-esteem among secondary school students in Selangor, Malaysia - Azman, Adibah (2018)
The purpose of the present study is to determine the relationship between personality type, aggressive behaviour and self-esteem among secondary school students in Selangor. As stated previously in past researchers, moral damage and behavioural problem among teenagers rise from year to year. Teenagers or to be precise in this study, secondary school students are a group of individuals who usually facing the challenges and problems. They are at the unstable stage and still in the process of shaping their identity and personality. Hence, the aims of this study is to investigate the personality type as well as self-esteem among the secondary school students with their aggressive behaviour. This study also aim to identify the mediation effect of self-esteem on the relationship between type of personality and aggressive behaviour. This research involved 400 secondary school students (200 male and 200 female) from state of Selangor.